Propuesta del proceso de producción para la fabricación de tejas mediante el aprovechamiento de los residuos de vidrio plano en la ciudad de Villavicencio (2021)
The increase in construction waste represents a considerable factor in affecting the environment, mainly in the face of limited or non-existent opportunities for use and reuse. Such is the case with solid flat glass waste, which although not directly consistent with the operations of the construction companies, if they are those companies that supply products in this material for that industry. In Villavicencio there is a considerable demand for flat glass which also represents considerable levels of solid waste of this material, which in the face of an inadequate arrangement can represent a considerable factor of environmental pollution, this research aims to propose a production system that allows the use of these wastes, to manufacture a product that serves as a substitute for conventional shingles.